PTU-103 Management of biliary complications following liver transplantation: a single centre experience. (17th June 2017) - Hegade, V; Tsirlis, T; Latimer, S; Charnley, R; Manas, D; Nayar, M; Oppong, K; Hudson, M; Leeds, JS
Abstract : Introduction: Biliary complications after liver transplantation (LT) are common and some risk factors have been identified. Optimum endoscopic management including use of fully covered self-expanding metal stents (fcSEMS) in patients following LT requires evaluation. We aimed to identify risk factors for biliary complications following LT and present our experience of endoscopic management. Method: Retrospective analysis of adult LT's performed at our centre. Patient demographics, donor characteristics, transplantation data (including graft type; donation after brain death (DBD) or cardiac death (DCD)), biliary complications and subsequent management were recorded and the DRI calculated. The cohort consisted of all DBD LT's performed between 2013 and 2016 and all DCD LT's performed between 2007 and 2016. Univariate and multivariable analysis was used to identify risk factors for biliary complications and ascertain factors associated with stricture resolution and ascertain factors associated with biliary stricture resolution. Results: A total of 153 (n=122 DBD and n=31 DCD) patients were included of which 43 (28%) patients developed biliary complications. There was no difference in the rate of biliary leaks but biliary strictures were associated with DCD (16/31, 51.6%) compared to DBD (27/122, 22.1%) OR 3.1 (1.6–8.6, p=0.0017), higher donor risk index (2.08 vs. 1.85, p=0.017) and warm ischaemia time >40 min (p=0.033). Late biliary strictures (>1 year) occurred more frequently in DCD compared to DBD livers (4/11 vs. 1/15 respectively). Hepatic artery thrombosis rate was the same in both groups (9.3% vs. 7.2%, p=0.74). Multivariable analysis showed that only DCD was independently associated with biliary strictures (adjusted OR 6.4, 2.4–17.0, p=0.0002). 11/43 with biliary complications underwent surgical or radiological management. The remainder underwent ERCP; 24 patients had 60 procedures for strictures, 6 patients had 17 procedures for biliary leak and 2 had 4 procedures for stone disease (all DCD). There were no differences in stricture resolution between DCD and DBD (7/11 vs. 11/13, p=ns) or the number of procedures required (32 in DBD vs. 28 in DCD). However, stricture resolution rates were higher following fcSEMS insertion compared to plastic stents (8/10 vs. 10/39 respectively, p=0.006). Conclusion: Biliary complications are associated with DCD livers, higher DRI and longer warm ischaemia time. Endoscopic management of biliary complications leads to high resolution rates but patients undergo a high volume of such procedures. fcSEMS appear to have improved efficacy for stricture resolution compared to plastic stents. Disclosure of Interest: None Declared